The effect of feeding soyabeans treated with different alkaline salts on the protein and energy utilisation by starter boilers - B. A., Ayanwale (Universiti Putra Malaysia Press, 2004)
An experiment was conducted to evaluate the effect of feeding alkaline treated soyabeans to broilers on protein and energy efficiency of the starter boilers. Soyabean seeds were soaked in aqueous solution (3% concentration) of sodium chloride, trona, and alum respectively for 24 hours, air-dried, ground and used in compounding the three treatments, sodium chloride treated soyabeans (T2), trona (T3), and alum (T4), with roasted soyabeans as the control (Tl). The results indicated that soaking soyabeans in alkaline salt solution slightly reduced DM, CF, NFE and GE while EE and Ash were lower in the roasted soyabean seeds. The PER values for Tl and T4 were similar and higher values while energy efficiency was improved in T3 and T4. At the end of the starter phase, the body weights and body weight gains of the broiler on diets in which soyabeans were treated with NaGI were poorer even compared to the other groups, which was partly attributed to the lower feed intake (P< O. 05) and poorfeed efficiency (p<0.05) of the group. The broilers fed trona and alum treated soyabeans had better energy efficiency ratio than the ones fed the NaGI treated soyabean and the control diets. It was concluded that any of the three alkaline salts could be used to process soyabeans for broiler consumption but for better energy and protein efficiency the utilization of trona and alum were preferable.